POTRET KERUKUNAN ANTAR ALIRAN KEAGAMAAN (Studi Kasus Jema’at Ahmadiyah dan NU di Desa Winong Banjarnegara Jawa Tengah) - Masthuriyah Sa’dan (Religi: Jurnal Studi Agama-agama, 2015)
This study explores harmonious lives among religious groups in the Winong village, Banjarnegara. It describes both religious and social lives including factors that reinforcing the creation of harmony among religious groups in the village. Based on Inter-religious harmony theories, the study shows that Winong is a village with differs cultures and religious communities but it is able to maintain harmony. The harmony among religious beliefs in Winong , as shown between the Ahmadis and NU community, is manifested not only in terms of toleration and passive co-existence, but also in the equality of all elements in the society which is embodied in the social, culture and the political lives.